1979
DOI: 10.1007/bf01869291
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes of membrane-bound (Na+−K+)-ATPase as revealed by antibody inhibition

Abstract: As different structural states of the (Na+-K+)-ATPase (EC 3.6.1.3) may lead to a changed reactivity to antibodies, the influence of Na+, K+, Mg++, Pi and ATP on the reaction between highly purified (Na+-K+)-ATPase and antibodies directed against the membrane-bound enzyme was measured. The antigen antibody reaction was registered by measuring the antibody inhibition of (Na+-K+)-ATPase activity. In the membrane-bound but not in the solubilized enzyme four different degrees of antibody inhibition were obtained at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…On the other hand, it was found similar to the results of Giotta, who performed trypsin digestion experiments with a solubilized (Na + -K +)-ATpase preparation [5], that in the absence of Mg ++ binding of ATP leads to a protection of the enzyme which is considered to be due to a structural change of the protein, whereas binding of ATP has no effect on the degree of antibody inhibition of (Na + -K+)-ATPase activity [14]. Different from the antibody inhibition experiments, in which different degrees of antibody inhibition were obtained in the presence of Na + or K + provided ATP plus Mg ++ were present [14], Na + and K + also showed different effects on the trypsin action if ATP but no Mg ++ was present. Thus, it can be concluded that Na + and K + modulate the (Na + -K +)-ATPase structure if ATP has bound-but in a different, probably more extensive manner -if ATP plus Mg + + have bound to the enzyme.…”
Section: Dependence Of the (Na + -K + I-a Tpase Structure On A Tp Andsupporting
confidence: 85%
See 3 more Smart Citations
“…On the other hand, it was found similar to the results of Giotta, who performed trypsin digestion experiments with a solubilized (Na + -K +)-ATpase preparation [5], that in the absence of Mg ++ binding of ATP leads to a protection of the enzyme which is considered to be due to a structural change of the protein, whereas binding of ATP has no effect on the degree of antibody inhibition of (Na + -K+)-ATPase activity [14]. Different from the antibody inhibition experiments, in which different degrees of antibody inhibition were obtained in the presence of Na + or K + provided ATP plus Mg ++ were present [14], Na + and K + also showed different effects on the trypsin action if ATP but no Mg ++ was present. Thus, it can be concluded that Na + and K + modulate the (Na + -K +)-ATPase structure if ATP has bound-but in a different, probably more extensive manner -if ATP plus Mg + + have bound to the enzyme.…”
Section: Dependence Of the (Na + -K + I-a Tpase Structure On A Tp Andsupporting
confidence: 85%
“…The trypsin digestion experiments demonstrated that different structural states of the (Na §247 molecule can be distinguished, which we have also shown by antibody inhibition studies [14]. Thus with both methods different enzyme conformations in the presence of Mg ++, ATP plus Na + and in the presence of Mg §247 ATP plus K + were detected, whereas no structural alterations of the enzyme specific to the addition of Na + or K + could be found in the absence of ATP.…”
Section: Dependence Of the (Na + -K + I-a Tpase Structure On A Tp Andmentioning
confidence: 64%
See 2 more Smart Citations
“…1974; Jean & Albers, 1977;Koepsell, 1978Koepsell, , 1979Kyte, 1974;Michael et al, 1977). However, because of the heterogeneous nature of these antibodies, the results of many of these studies have been confusing and, in some cases, contradictory.…”
mentioning
confidence: 99%